Gangs and organized crime - Knox, George W. (Routledge, 2019)
Gang and organized crime history and foundations -- Los Angeles area street gangs -- Chicago area street gangs -- Outlaw motorcycle gangs -- Prison gangs -- Females in the gang world -- Gangs and violence -- Gangs and the military -- Asian, East Asian, and African organized crime -- Italian organized crime -- Russian and other European organized crime -- Drug and other trafficking organizations in the Americas -- Investigation and prosecution of gangs and organized crime groups